2021
DOI: 10.1002/smll.202101839
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Defects Change the Correlation between Photoluminescence, Ideality Factor, and Open‐Circuit Voltage in Perovskite Solar Cells

Abstract: The ideality factor (nid) and photoluminescence (PL) analyses assess charge recombination characteristics in perovskite solar cells (PeSCs). However, their correlations with open‐circuit voltage (Voc) are often found to be complicated depending on the recombination types in the devices. Herein, the correlation of nid, PL characteristics and Voc is elucidated depending on the interfacial crystal quality in triple‐cation mixed‐halide perovskite, Cs0.05(MA0.17FA0.83)0.95Pb(I0.83Br0.17)3, deposited on different ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…The PCE for the champion device with a C3 SRL is among the highest reported for inorganic CsPbI 3 PSCs to-date. ,, , The enhancement of PCE with the insertion of an SRL with increasing alkyl chain length is due primarily to progressive increases in open-circuit voltage ( V OC ) from 1.05 V (no SRL) to 1.06 V (C0), 1.10 V (C2), and 1.18 V (C3) and a fill factor (FF) from 74% (no SRL) to 75% (C0), 76% (C2), and 82% (C3). This increase in V OC and FF with increasing alkyl chain length is consistent with a more rapid PL decay and implicates that solar cell performance improvements stem from fewer interfacial defects and improved carrier extraction at the perovskite/ETL interface. ,, Since film morphology can also affect V OC and FF, scanning electron microscopy (SEM) was employed to examine the surface topology. , No noticeable difference in surface topology is observed across these samples (Figure S5). In addition, ultraviolet photoemission spectroscopy (UPS) was also used to study if enhancements in the V OC and FF stem from TiO 2 work function changes with SRL incorporation. , The work functions of these surfaces are comparable within the error of measurement and show no correlation with SRL alkyl chain length or PSC performance (Figure S3).…”
mentioning
confidence: 66%
“…The PCE for the champion device with a C3 SRL is among the highest reported for inorganic CsPbI 3 PSCs to-date. ,, , The enhancement of PCE with the insertion of an SRL with increasing alkyl chain length is due primarily to progressive increases in open-circuit voltage ( V OC ) from 1.05 V (no SRL) to 1.06 V (C0), 1.10 V (C2), and 1.18 V (C3) and a fill factor (FF) from 74% (no SRL) to 75% (C0), 76% (C2), and 82% (C3). This increase in V OC and FF with increasing alkyl chain length is consistent with a more rapid PL decay and implicates that solar cell performance improvements stem from fewer interfacial defects and improved carrier extraction at the perovskite/ETL interface. ,, Since film morphology can also affect V OC and FF, scanning electron microscopy (SEM) was employed to examine the surface topology. , No noticeable difference in surface topology is observed across these samples (Figure S5). In addition, ultraviolet photoemission spectroscopy (UPS) was also used to study if enhancements in the V OC and FF stem from TiO 2 work function changes with SRL incorporation. , The work functions of these surfaces are comparable within the error of measurement and show no correlation with SRL alkyl chain length or PSC performance (Figure S3).…”
mentioning
confidence: 66%
“…Our previous study on the correlation between V oc and PL characteristics revealed that PL emission might be insufficient to support a loss of V oc by nonradiative recombination in interface‐limited solar cells because PL from the bulk is as important as PL from the interface in determining total emission. [ 20 ] Nevertheless, the modest difference in PL indicates that overall crystal qualities of perovskites are better when deposited on MWA‐NiO x , which we attribute to the low composition of Ni >3+ .…”
Section: Resultsmentioning
confidence: 93%
“…[ 17,18 ] However, strong interfacial recombination and shrinkage of quasi‐Fermi‐level splitting by a large mismatch in energy levels limit the open‐circuit voltage ( V oc ). [ 19–21 ] Moreover, the electrical conductivity of stoichiometric NiO, which is a charge‐transfer insulator with partial Mott−Hubbard character, is intrinsically limited because the valence band maxima consist of localized O 2 p orbitals. [ 22–24 ] The Ni deficiency from NiO is a key factor in enhancing the electrical conductivity by the release of holes from the nickel vacancies or the occupation of substitutional metal cations into nickel sites in the NiO host lattice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic–inorganic metal halide perovskite solar cells (PSCs) have shown great potential to become a revolutionary photovoltaic technology, owing to their advantages of being cost-effective, ease of fabrication, and considerable power conversion efficiency (PCE) during the past decade. , Thanks to the excellent photoelectric properties of perovskite materials, such as tunable energy bands via composition engineering, long diffusion length (>1 μm), high absorption coefficient (∼10 5 cm –1 at visible range), and high defect tolerance, laboratory-scale PSCs have made tremendous achievements, reaching a certified PCE as high as 25.5% . Such a rapid development is unprecedented for any other photovoltaic materials.…”
Section: Introductionmentioning
confidence: 99%